QORAQALPOG‘ISTONDA MAKTAB TA’LIMI TIZIMINING RIVOJLANIShI VA JOYLAShUVI XUSUSIYATLARI - Uzakbaev, K.K.; Turgʻanbaev, D.N. (SCIENCE and SOCIETY, 2025)
The article describes the organization and distribution of the school education system in the Republic of Karakalpakstan.
Keywords: public services; preschool education; number of children; preschool educational organizations; service radius; urban planning norms and rules